Both Sides Now: Report on ambiguity and sustainability in international projects in higher arts education - Ölme, Rasmus; Wos, Marie (Peripeti, 2022)
Based on practical experiences, the authors reflect upon potentials and paradoxes involved in employing sustainability as core concept in international educational art projects. Inspired by ecological thinking (Morton 2021) and ambiguity (Gielen 2020), they propose international exchange as a prosperous context for developing complex and nuanced understandings of current problematics of contemporary life.